Increased Expression of Escherichia coli Polynucleotide Phosphorylase at Low Temperatures Is Linked to a Decrease in the Efficiency of Autocontrol - Mathy, N. (American Society for Microbiology, 2001)
Polynucleotide phosphorylase (PNPase) synthesis is translationally autocontrolled via an RNase III-dependent mechanism, which results in a tight correlation between protein level and messenger stability. In cells grown at 18°C, the amount of PNPase is twice that found in cells grown at 30°C. To investigate whether this effect was transcriptional or posttranscriptional, the expression of a set of pnp-lacZ transcriptional and translational fusions was analyzed in cells grown at different temperatures. In the absence of PNPase, there was no increase in pnp-lacZ expression, indicating that the increase in pnp expression occurs at a posttranscriptional level. Other experiments clearly show that increased pnp expression at low temperature is only observed under conditions in which the autocontrol mechanism of PNPase is functional. At low temperature, the destabilizing effect of PNPase on its own mRNA is less efficient, leading to a decrease in repression and an increase in the expression level.